(untitled) (Journal of Contemporary Educational Policies and Practices, 2022)
Tasks are frequently used in English as a Foreign Language (EFL) classes. The sociocultural theory considers tasks to mediate learners through language. However, how a specific task can embrace such a claim remains an issue to explore. This study was set out to address the questions of how a decision making task stimulated interaction among peers and how it mediated knowledge construction. Thirty EFL junior college students forming fifteen pairs participated in the study. The recorded videos of their decision-making task performance were used for data analysis. The findings reveal that cumulative talk was present in all pairs’ recordings. While exploratory talk was not generated as frequently as cumulative talk, it tended to conduce to more language learning and knowledge construction. The findings also indicate that with the same task, peers interacted in different patterns and mediated each other by providing immediate assistance with English vocabulary and ideas.